Understanding fall risk factors in community-dwelling older adults: A cross-sectional study. - Carrasco, C. (2020)
Background: Ageing process is inherently associated with physiological decline and consequently with an increased risk for falling. Identification of risk factors according to the population studied is crucial to design and implement effective programs for the prevention of falls in elderly. Material and Methods: A total of 508 older adults (113 males and 395 females) were enrolled in a cross-sectional study. Assessment of the risk factors for falls was performed by using questionnaires (basic data and health-related information) and morphofunctional evaluations (strength and flexibility of lower body and dynamic balance). Results: A significantly greater proportion of women experienced fall episodes within the past year (83.9% vs. 73.1% in the non-fall subgroup; p<0.04). In addition, certain chronic diseases were detected to be significantly more prevalent in the fall subgroup compared to the non-fall subgroup, such as depression (21.6% vs. 13.5%; p= 0.017), osteoporosis (15.6% vs. 9.0%; p= 0.023), arthrosis (32.1% vs. 22.1%; p= 0,012), arthritis (6.0% vs. 2.1%; p= 0.023), poliomyelitis (6.4% vs. 2.4%; p= 0.025) and fibromyalgia (2.3% vs. 0,3%; p= 0.045); comorbidity (≥3 conditions) and diabetes appeared as other potentially important falls risks factors, but did not reach statistical significance (p=0.067 and p=0.066, respectively). With regard to morphofunctional variables, the non-fall subgroup showed significantly better scores of lower-body strength (13.22±4.6 vs. 11.83±4.7 nº of stands/30 sec; p= 0.001) and dynamic balance (6.91±2.4 vs. 7.63±2.6 sec; p= 0.002) than the fall subgroup. Multivariate regression analysis revealed that greater lower-body strength significantly reduced the occurrence of fall(s) (AOR 0.955, 95% CI 0.910-1.002). Conclusions: Lower-body strength was the most significant risk factor for fall event(s) within the past year, likely influenced by the concurrent presence of debilitating diseases. Exercise interventions focused on improve walking, muscle strength, and balance would be highly recommended to reduce falls and subsequent disability in elderly people.